The almost nearly perfect people behind the myth of the Scandinavian utopia - Booth, Michael (New York Picador, 2014)
A witty, informative, and popular travelogue about the Scandinavian countries and how they may not be as happy or as perfect as we assume, ?The Almost Nearly Perfect People offers up the ideal mixture of intriguing and revealing facts? (Laura Miller, Salon).
Includes index.
Keywords: Scandinavians